Compendium of documents on National Human Rights Institutions in eastern and southern Africa - Charles M Fombad (Pretoria University Law Press (PULP), 2019)
Africa's increasing recognition and protection of human rights have been accompanied by a surge in the number of NHRIs established with broad mandates to promote and protect human rights. The mandates and powers of the NHRIs vary from country to country, as does their ability to deliver on these mandates. Indeed, the rapid increase in the number of NHRIs in Africa has come with a variety of substantive and operational challenges. In the face of such challenges, those who work in NHRIs need to understand the broader regional and global context in which the institutions operate and the changing nature of human rights issues. This compendium provides an overview of NHRIs in eastern and southern Africa. It is guided to a large extent by the internationally agreed-upon Principles Relating to the Status of National Institutions, referred to as the Paris Principles. These Principles are broadly accepted as the benchmark against which the legitimacy and credibility of NHRIs can be assessed. Endorsed by the United Nations General Assembly in 1993, the Paris Principles provide NHRIs with guidelines as to their competence and responsibilities, their composition and guarantees of independence and pluralism, and their methods of operation; additional principles relate to the status of commissions with quasi-jurisdictional competence. The generous financial support of the Konrad Adenauer Stiftung, Rule of Law for Sub-Saharan Africa, Nairobi, Kenya office, is gratefully acknowledged.